Odpowiedź :
Odpowiedź:
1 i 5/6 + 1/2 = 1 i 5/6 + 3/6 = 1 i 8/6 = 2 i 2/6 = 2 i 1/3
1 i 5/6 + 2/3 = 1 i 5/6 + 4/6 = 1 i 9/6 = 2 i 3/6 = 2 i 1/2
1 i 5/6 + 2 i 1/12 = 1 i 10/12 + 2 i 1/12 = 3 i 11/12
1 i 5/6 + 1 i 3/4 = 1 i 10/12 + 1 i 9/12 = 2 i 19/12 = 3 i 7/12
1 i 5/6 + 1 i 1/5 = 1 i 25/30 + 1 i 6/30 = 2 i 31/30 = 3 i 1/30
1 i 5/6 + 2 i 7/8 = 1 i 20/24 + 2 i 21/24 = 3 i 41/24 = 4 i 17/24
1 i 5/6 + 3 i 4/9 = 1 i 15/18 + 3 i 8/18 = 4 i 23/18 = 5 i 5/18
1 i 9/10 - 3/5 = 1 i 9/10 - 6/10 = 1 i 3/10
2 i 1/15 - 3/5 = 2 i 1/15 - 9/15 = 1 i 16/15 - 9/15 = 1 i 7/15
1 i 1/3 - 3/5 = 1 i 5/15 - 9/15 = 20/15 - 9/15 = 11/15
3/4 - 3/5 = 15/20 - 12/20 = 3/20
4 i 1/2 - 3/5 = 4 i 5/10 - 6/10 = 3 i 15/10 - 6/10 = 3 i 9/10
5 i 7/20 - 3/5 = 5 i 7/20 - 12/20 = 4 i 27/20 - 12/20 = 4 i 15/20 = 4 i 3/4
1 i 3/7 - 3/5 = 1 i 15/35 - 21/35 = 50/35 - 21/35 = 29/35
Odpowiedź:
a)
[tex]\frac{1}{2} +1\frac{5}{6} =\frac{3}{6} +1\frac{5}{6} =1\frac{8}{6} = 2\frac{2}{6} =2\frac{1}{3}[/tex]
[tex]\frac{2}{3} +1\frac{5}{6} =\frac{4}{6} +1\frac{5}{6} =1\frac{9}{6} = 2\frac{3}{6} =2\frac{1}{2}[/tex]
[tex]2\frac{1}{12} +1\frac{5}{6} =2\frac{1}{12} +1\frac{10}{12} =3\frac{11}{12} \\\\ 1\frac{3}{4} +1\frac{5}{6} = 1\frac{9}{12} +1\frac{10}{12} =2\frac{19}{12} = 3\frac{7}{12} \\\\ 1\frac{1}{5} +1\frac{5}{6} =1\frac{6}{30} +1\frac{25}{30} = 2\frac{31}{30} =3\frac{1}{30}[/tex]
[tex]2\frac{7}{8} +1\frac{5}{6} =2\frac{21}{24} +1\frac{20}{24} =3\frac{41}{24} =4\frac{17}{24} \\\\ 3\frac{4}{9} +1\frac{5}{6} =3\frac{8}{18} +1\frac{15}{18} =4\frac{23}{18} = 5\frac{5}{18}[/tex]
b)
[tex]1\frac{9}{10} -\frac{3}{5} = 1\frac{9}{10} -\frac{6}{10} =1\frac{3}{10} \\\\ 2\frac{1}{15} -\frac{3}{5} = 2\frac{1}{15} -\frac{9}{15} =1\frac{16}{15} -\frac{9}{15} =1\frac{7}{15}[/tex]
[tex]1\frac{1}{3} -\frac{3}{5} =1\frac{5}{15} -\frac{9}{15} =\frac{20}{15} -\frac{9}{15} = \frac{11}{15} \\\\ \frac{3}{4} -\frac{3}{5} =\frac{15}{20} -\frac{12}{20} =\frac{3}{20}[/tex]
[tex]4\frac{1}{2} -\frac{3}{5} =4\frac{5}{10} -\frac{6}{10} = 3\frac{15}{10} -\frac{6}{10} =3\frac{9}{10} \\\\ 5\frac{7}{20} -\frac{3}{5} =4\frac{27}{20} -\frac{12}{20} =4\frac{15}{20} = 4\frac{3}{4} \\\\ 1\frac{3}{7} -\frac{3}{5} =1\frac{15}{35} -\frac{21}{35} = \frac{50}{35} -\frac{21}{35} =\frac{29}{35}[/tex]